Peer Review of Educational Scholarship Faculty Development Workshop - Kevin Souza (Association of American Medical Colleges, 2008)
Abstract This resource is a workshop developed by the University of California, San Francisco (UCSF), to educate faculty about their ability to have enduring educational materials peer-reviewed and published through a rigorously established peer review process. The workshop reviews the history of educational scholarship and helps faculty think about their own scholarship and its value. Faculty may use as much or as little of this workshop as is helpful to their institution. Sections of this workshop can be presented on their own, as is relevant to the situation. Faculty participants can also review their own material instead of predefined materials if that is their preference. Participants often bring ideas they are working on, and it is important to find out and address those topics or materials throughout the workshop. Ratings of this workshop by participants have ranged between 4 and 5 on a 5-point scale, with a 5 rating being outstanding. This workshop has been offered three times at UCSF, and feedback from those sessions has been incorporated, where appropriate, into this version. This includes the fifth objective stating that "participants will be able to access local resources to help them package and submit materials for review," assuming that their institution has some resources, if only consultative, for faculty to access in packaging or development materials for peer review.